2023
DOI: 10.3390/w15101909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar on Soil-Water Characteristics of Soils: A Pore-Scale Study

Abstract: The mechanical and hydraulic properties of soils are largely governed by their soil-water characteristics, which are influenced by factors such as pore size distribution (PSD). While biochar is commonly used as an additive to alter soil properties, its effect on PSD and the soil water retention curve (SWRC) at the pore scale remains unclear. This study aims to investigate the impact of biochar on PSD and SWRC in soils of different types. The study utilized nuclear magnetic resonance (NMR) and the filter paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…In the case of biochar, this can be explained by the small surface area measured on the biochar (Table 1), since the permanent wilting point is closely related to the specific surface area of soil [36,37]. This is in agreement with Chen et al [38], which showed that the addition of biochar had little effect on soil water contents at a matric potential of higher than 10,000 hPa (pF > 4). Amendment with biochar led to a significant increase in AWC for A1 and A2 soils but not for the original soil A (Figure 3).…”
Section: Available Water Capacitysupporting
confidence: 86%
“…In the case of biochar, this can be explained by the small surface area measured on the biochar (Table 1), since the permanent wilting point is closely related to the specific surface area of soil [36,37]. This is in agreement with Chen et al [38], which showed that the addition of biochar had little effect on soil water contents at a matric potential of higher than 10,000 hPa (pF > 4). Amendment with biochar led to a significant increase in AWC for A1 and A2 soils but not for the original soil A (Figure 3).…”
Section: Available Water Capacitysupporting
confidence: 86%
“…The hydrophysical properties of soil, such as porosity, saturated hydraulic conductivity, soil water repellency, and water retention capacity, are the most important factors that affect the soil environment. Some authors found that the soil water retention capacity and porosity increased in sandy soil after biochar amendment [7][8][9] decreased saturated hydraulic conductivity and bulk density [10,11] and had no effect on soil water repellency [12] or altered it [13,14]. The impact of biochar on clayey soil is studied to a lesser extent, and the results are different.…”
Section: Introductionmentioning
confidence: 99%